Severe Potential Drug-Drug Interactions and the Increased Length of Stay of Children in Intensive Care Unit - Lima, Elisangela da Costa; Camarinha, Barbara Dias; Ferreira Bezerra, Nathalia Cristina; Panisset, Anderson Gonçalves; Belmino de Souza, Raquel; Silva, Marcus Tolentino; Lopes, Luciane Cruz (Frontiers in Pharmacology, 2020)
Children are exposed to drug-drug interactions (DDI) risks due to their organism's complexity and the need for several medicines prescriptions in pediatric intensive care units (PICU). This study aimed to assess the prevalence of potential DDIs in a Brazilian PICU. We carried out a cross-sectional study at a pediatric teaching hospital from Rio de Janeiro (Brazil) over one year. Potential DDIs (pDDIs) between prescribed medicines for hospitalized children in PICU (n=143) were analyzed according to severity using Micromedex®. Sex, age group, number of drugs prescribed, vasoactive amines use (a proxy of clinical complexity), and the PICU length of stay were summarized using descriptive statistics. Association between the PICU length stay, and variables sex, age, clinical condition complexity, number of drugs prescribed, and severity of pDDI were examined by univariate and multiple linear regression. Seventy percent of patients aged three days to 14 years old were exposed at least one potential DDIs during PICU stay. Two hundred eighty-four different types of pDDIs were identified, occurring 1,123 times. Nervous system drugs were implicated in 55% of the interactions, and fentanyl (10%) was most involving in pDDIs. Most pDDIs were classified as higher severity (56.2%), with reasonable documentation (64.6%) and unspecified onset time (63.8%). Worse clinical condition, ten or more drugs prescribed, and most severe pDDIs were associated with a longer PICU length of stay. Multiple linear regression analysis showed an increase of 9. 83 days (95% confidence interval: 3.61 – 16.05; p = 0.002) in the PICU length of stay in children with major or contraindicated pDDIs. The results of this research may support the monitoring and prevention of pDDIs related to adverse events in children in intensive care and the design and conduction of new studies.